Overall survival of transplant eligible patients with newly diagnosed multiple myeloma: comparative effectiveness analysis of modern induction regimens on outcome - Paquin, Ashley R. (Blood Cancer J, 2018)
Overall survival (OS) of multiple myeloma has improved remarkably over time, with the recent Intergroupe Francophone du Myelome (IFM) 2009 randomized trial reporting a 4-year OS rate of approximately 82% in patients receiving modern therapy. However, survival estimates from clinical trials may overestimate outcomes seen in clinical practice even with the adjustment for age and other key characteristics. The purpose of this study was to determine the OS of myeloma patients seen in routine clinical practice who resembled the cohort studied in the IFM 2009 trial. A second goal was to conduct a brief comparative effectiveness analysis of bortezomib, lenalidomide, dexamethasone, and other major induction regimens used during the study period. We studied all patients with myeloma 65 years of age and younger, seen at the Mayo Clinic between January 1, 2010 and August 31, 2015, who had a stem cell harvest performed within 12 months of initial diagnosis. Patients with baseline serum creatinine >2 mg/dL were excluded. Five hundred and eighteen patients were studied. The 4-year OS rate was 82.3%, comparable to results achieved in the contemporaneous IFM randomized trial. The 4-year OS rates for standard and high-risk myeloma were 86.3% and 68.2%, respectively.